Psikologi Fomo Gen-Z Dalam Pembelian Impulsif: Analisis Perilaku Religiusitas Konsumen Muslim - Muammar W. Maruapey; Fadli F. Malawat; Fatmah Watty Pelupessy; Afdhal Yaman; Hanifah Hanifah; Arizal Hamizar (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to analyze the influence of the Fear of Missing Out (FOMO) phenomenon on impulsive buying behavior among Muslim Gen Z in the digital era. Muslim consumers from Generation Z face a unique challenge in balancing the desire to remain socially relevant with Islamic principles that emphasize simplicity and self-control. The method used is qualitative with a case study design. Primary data were collected through in-depth interviews with Muslim Gen Z respondents in Ambon City who experience FOMO and exhibit impulsive buying tendencies. Secondary data were obtained from relevant scientific literature and other sources that support the research context. Data analysis was conducted using data reduction techniques, narrative and visual data presentation, and verification to ensure the validity of the findings. The study results indicate that FOMO plays a significant role in driving impulsive buying behavior among Muslim Gen Z, with intensity influenced by social media exposure and social norms. However, religiosity levels also influence respondents in controlling their impulsive tendencies. Respondents with higher religiosity levels tend to be more critical of consumerist impulses, although some still feel social pressure to follow trends.